Ultrahigh Storage Capacity of Alkali Metal Ions in Hexagonal Metal Borides with Orderly Multilayered Growth Mechanism - Jiaxin Jiang; Hongyan Guo; Ning Lu (Nanomaterials)
The global energy shortage and the gradual depletion of lithium resources have become increasingly prominent. Improving the energy density of lithium-based secondary batteries and developing other high-performance alkali-metal secondary batteries have become the research focus. In this study, two-dimensional (2D) hexagonal metal borides (h-MBenes) are investigated as ordered alkali metal adsorption substrates for alkali-metal-based battery anode materials using density functional theory (DFT). Twelve thermodynamically stable h-MBenes are screened out from thirty-three structures, and their excellent stability and metallic electronic characteristics are confirmed. The ordered multilayered growth in alkali metal adsorption is found to depend on two factors: low lattice mismatching and dynamic matching of the work function. In particular, Mg/Al/V-based h-MBenes exhibit excellent lithium lattice matching (<3.35% mismatch), enabling layer-by-layer hexagonal (001) Li growth for ≥5 layers. They have ultrahigh lithium capacities (2170–3818 mAh·g−1), low migration barriers (0.01–0.05 eV), and low voltages (0.003–0.714 V). Mg/Y-based h-MBenes enable three Na layers’ adsorption with a capacity of 1717/605 mAh·g−1, and Al2B2 achieves a 472 mAh·g−1 potassium storage capacity, respectively. Due to the orderly multilayered growth mechanism, Mg/Al/V-based h-MBenes show great potential as high-safety and ultrahigh-capacity alkali-metal battery anode materials.